(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The study aimed to identify the impact of strategic control on organizational performance in the Jordanian Islamic Bank. The study showed the dimensions of strategic control represented in (setting standards, measuring actual performance, evaluating strategic performance, taking corrective actions), and the dimensions of organizational performance represented in (learning and growth, Achieving objectives, customer satisfaction), the random sample consist of (102) employees working in the Jordanian Islamic Bank. The study used the descriptive analytical approach, and reached a set of results, the most important are: the attitudes of study sample towards the independent variable strategic control came positive with high degree, and the dependent variable organizational performance came positive with high degree, also the results showed there is a statically significant impact of strategic control dimensions on organizational performance. As well the dimensions of strategic control do not constitute an equal amount of relative importance in the Jordanian Islamic Bank. Accordingly, the study recommended the necessity of acquiring and applying the modern strategic control mechanisms by the Jordanian Islamic Bank to enhance and develop performance, provide a safe work environment, overcome errors, and achieve a competitive advantage. In the banking markets.